PERAN KEPEDULIAN PADA LINGKUNGAN DALAM MEMEDIASI PENGARUH GREEN MARKETING TERHADAP NIAT PEMBELIAN PRODUK RAMAH LINGKUNGAN - Supandini, Putu Ari; Pramudana, Komang Agus Satria (E-Jurnal Manajemen, 2017)
Consumer conciousness to maintain environment is increasing at this time. This reseach aims to exam the impact   of green market willing to purchase eco friendly environment product mediated by careness of cosmetic study of the body shop brand. Data collection on this reseach use likert scale quesioner. The amount of sample are 100 respondents and use porposive sampling technic.data analysis technic that used are deskriptif statistic and inferensial statictic. Deskriptif statistic explain profile of respondents, while statistic inferensial is confirmatory analysis, track analysis and sobel test is used to test the patterned hypothesis. The exam result shows that green marketing significantly impact to awareness of environment and also impact the willingness to buy eco friendly environment product. Attention to environment significanly can mediate the impact of green marketing to have willingness to buy eco friendly environment product of the body shop brand